Association of Dietary Inflammatory Index (DII) with disease activity and inflammatory cytokines in the patients with rheumatoid arthritis. Issue 11 (20th September 2021) - Tandorost, Arash; Kheirouri, Sorayya; Moludi, Jalal; Seyedmardani, Seyedmostafa
Abstract: Objectives: This study aimed, at first, to assess Dietary Inflammatory Index (DII) in participants with rheumatoid arthritis (RA) and compare them with healthy controls. Then, to evaluate the association of DII with the risk of RA occurrence, the severity of disease, and systemic inflammation. Methods: This case‐control study enrolled 100 newly diagnosed cases with RA and 100 age and sex‐matched healthy controls. DII was computed based on the individuals' FFQ‐derived dietary data. Serum levels of inflammatory markers, including the high sensitivity C‐reactive protein (hs‐CRP) and Tumour Necrosis Factor‐alpha (TNF‐α), were measured using the ELISA method; and the severity of the disease was assessed based on the disease activity score 28 (DAS‐28). Results: The mean DII score was higher in the RA patients as compared with that in the controls (0.66 ± 0.23 vs. −0.58 ± 0.19, P  = .002). Patients with the highest DII had significantly higher serum inflammatory (hs‐CRP and TNF) and clinical markers (DAS‐28 score and the number of tender joints). A significant univariate relationship between DII score and risk of RA incident [6.48 (95% CI: 1.79 to 23.44)] disappeared in multivariate analysis. For each 1‐unit increase in DII, the DAS‐28 score was raised by 1.11 times ( P  = .001). Conclusion: An inflammatory diet may act as a potential risk factor contributing to the development of RA and its severity. Therefore, dietary modification with the goal of reducing the DII score could be a beneficial strategy to improve the clinical outcomes in such patients.